Effect of Citrus Flavanones on Diabetes: A Systematic Review - Azhar, Sameen; Sabahat, Ribka; Sajjad, Rameen; Nadeem, Fatima; Amjad, Aruba; Hafeez, Nawal; Nayab, Taram; Wahid, Saba; Tanweer, Afifa (Current Diabetes Reviews, 2023)
Background: Fruits and vegetables play a significant role in the health and nutrition of human beings. Flavanones being the major class of flavonoids are the main phytochemicals in citrus fruits having several favorable effects, particularly in preventing diabetes. Objective: The purpose of this systematic review was to discuss the anti-diabetic potential of citrus flavanones based on in vivo studies. Methods: A search of Google Scholar, PubMed, NCBI, Research Gate, Science Direct, HEC Digital Library databases for articles that have been published since 2010 was conducted using the keywords citrus, flavanones, and diabetes. Results: A total of 10 articles were identified, in which it was reported that 5 flavanones have antidiabetic effects. These flavanones have many benefits, such as they help in glycemic control, regulate the biomarkers of lipid profile, renal function, and modulate the signaling pathways that increase insulin sensitivity and uptake of glucose, thus are responsible for preventing diabetes and complications related to it. Conclusion: Therefore, citrus flavanones are the candidates having promising anti-diabetic potential but their effect needs to be verified through human studies.
Keywords: Diabetes